2021
DOI: 10.18632/aging.202943
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key pathways and genes in carotid atherosclerosis through bioinformatics analysis of RNA-seq data

Abstract: While acknowledging carotid atherosclerosis (CAS) as a risk factor for ischemic stroke, reports on its pathogenesis are scarce. This study aimed to explore the potential mechanism of CAS through RNA-seq data analysis. Carotid intima tissue samples from CAS patients and healthy subjects were subjected to RNA-seq analysis, which yielded, 1,427 differentially expressed genes (DEGs) related to CAS. Further, enrichment analysis (Gene Ontology, KEGG pathway, and MOCDE analysis) was performed on the DEGs. Hub genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…RNA-seq data has been used to analyze the underlying mechanism of carotid atherosclerosis (CAS). Differential and functional enrichment analysis of sequencing data from CAS patients and control group showed that inflammation and immune response were the potential pathogenesis of CAS, and significant DEGs CCR5 , NPY , and NPY5R were potential therapeutic targets of CAS ( Li et al, 2021 ). The method is also often used to study cancer therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq data has been used to analyze the underlying mechanism of carotid atherosclerosis (CAS). Differential and functional enrichment analysis of sequencing data from CAS patients and control group showed that inflammation and immune response were the potential pathogenesis of CAS, and significant DEGs CCR5 , NPY , and NPY5R were potential therapeutic targets of CAS ( Li et al, 2021 ). The method is also often used to study cancer therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that inhibiting NF-κB phosphorylation significantly reduces the inflammatory response and improves AS. [51,52] However, there are some limitations to network pharmacology. When we use network pharmacology to study the efficacy of active ingredients in prescription decoctions, the method simply superimposes the chemical constituents of single herbs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that inhibiting NF-κB phosphorylation significantly reduces the inflammatory response and improves AS. [51,52]…”
Section: Discussionmentioning
confidence: 99%